Evaluation of Application Methods of Metam Sodium for Management of Fusarium Crown and Root Rot in Tomato in Southwest Florida - McGovern, R J (Plant disease, 1998)
Experiments were conducted during 1992 to 1995 to evaluate the effectiveness of application methods of metam sodium (MS; sodium N-methyldithio-carbamate) for the management of Fusarium crown and root rot (FCRR) caused by Fusarium oxysporum f. sp. radicis-lycopersici in mulched and staked tomatoes (Lycopersicon esculentum Mill.) grown on raised beds in commercial fields in southwest Florida. Efficacy of MS was compared with soil-injection of methyl bromide-chloropicrin (MBC), the current industry practice for production of tomatoes in Flor-ida. The incidence of FCRR was consistently high in nontreated plots (80 to 100%), but disease severity varied by site, and yields were reduced by 10 to 57% at sites with high disease severity when compared to sites treated with MBC at 336 to 448 kg/ha. Application of MBC reduced FCRR incidence in all experiments. Chemigation with MS at 701 or 935 liters/ha into mulched beds using either one or two drip irrigation tubes placed on the soil surface, and soil injection of MS at 935 liters/ha, failed to reduce the disease. The application of MS at 935 liters/ha to the soil surface prior to bed formation produced variable results. Rotovation of MS at the same rate into preformed beds consistently produced reductions in the incidence of FCRR equivalent to those achieved by MBC